NUMERICAL AND EXPERIMENTAL TECHNIQUES IN ANALYZING FLOW STABILITY IN HEAT AND MASS TRANSFER - Dr. Dupadahalli Basavaraja (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The accurate analysis of flow stability in heat and mass transfer systems is crucial for optimizing engineering processes and ensuring efficient performance. This article provides a comprehensive review of numerical and experimental techniques used to study flow stability. It explores the principles of Computational Fluid Dynamics (CFD) and experimental methods such as Particle Image Velocimetry (PIV) and Laser Doppler Anemometry (LDA). The paper discusses the advantages and limitations of each approach and highlights their applications in various engineering fields. By integrating these techniques, researchers can achieve a more accurate understanding of flow behaviour and stability.